การพัฒนาตนเองของครูเกี่ยวกับการจัดการเรียนการสอนในหลักสูตรวิชาชีพระยะสั้นตามการรับรู้ของผู้บริหารและครูวิทยาลัยการอาชีพ ในเขตภาคเหนือ - สุรัสวดี ศรีมาลา (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of the research were : 1) To study and compare the perception level of problems state and self development technique of instructors concerning learning and teaching of vocational short course programs as perceived by administrators and instructors of industrial and community education colleges in the northern region in curriculum, teaching-learning activities, teachers, teaching-learning media, measurement and evaluation and teaching space and workshop and study. 2) To study and to compare state the problems state and self development on leaching of instructors concerning of vocational short course programs as perceived by administrators and instructors of industrial and community education colleges in the northern region as perceived by administrators and instructors with different gender, age, marital status, education level and working experience. The populations of this study consisted of 91 administrators and 220 instructors. The total number was 311. The datas were collected by using questionnaires with rating scales and were analyzed by using percentages, means, standard deviations, t-test, one-way analysis of variance and secheffe multiple comparison method. The major findings of this study were as follows: 1.To study the provision and instructors’ self development concerning instructional organization of vocational short course programs as perceived by administrators and instructors of industrial and community education colleges in the northern region. Were found at the moderate level. 2.The perception of provision and self development of instructors concerning learning and teaching of vocational short course as perceived by administrators and instructors of industrial and community education colleges in the northern region in curriculum, teaching-learning activities, teachers, teaching-learning media, measurement and evaluation, and teaching space and workshop showed a significant difference at the 0.05 level. 3.The perception of problems state and self development technique of instructors concerning instructional organization of vocational short course programs as perceived by administrators and instructors of industrial and community education colleges in the northern region as perceived by administrators and instructors with different gender, age, marital status, education level and working experience. 3.1The perception of problems state of instructors concerning learning and teaching of vocational short course as perceived by administrators and instructors of industrial and community education colleges in the northern region. There were no statistically significant among different marital status among the samples. However there was a statistically significant difference between administrators and instructors and instructors in the aspect of gender, age, education level and working experience at the 0.5 level. 3.2The perception of self development of instructors concerning learning and teaching of vocational short course as perceived by administrators and instructors of industrial and community education colleges in the northern region. There were no statistically significant among different gender, age and working experience among the samples. However there was a statistically significant difference between administrators and instructors and instructors in the aspect of marital status and education level at the 0.5 level,